Non-contrast versus contrast-enhanced MR in the diagnosis of spondylitis: A quantitative concordance-analysis - Prasetyo, Marcel (Eur J Radiol Open, 2020)
INTRODUCTION: : Magnetic Resonance (MR) imaging using gadolinium contrast media is an essential imaging modality in diagnosing spondylitis. However, gadolinium contrast is not widely available in Indonesia and relatively expensive. Many MR studies in Indonesia are performed without contrast administration. It is unclear how confident non-contrast MR can diagnose tuberculous spondylitis in comparison to standard contrast MR. PURPOSES: : This study aims to evaluate the concordance between the contrast MR and non-contrast spine MR in diagnosing tuberculous spondylitis. We also evaluate the interobserver agreement between the general radiologist and musculoskeletal radiologist in interpreting non-contrast MR of spondylitis. MATERIALS AND METHODS: : A cross-sectional study using secondary data was performed to evaluate the concordance between the MR results regarding the usage of contrast media in diagnosing spondylitis. The inclusion criteria were patients over 17 years old who underwent complete sequences of contrast-enhanced MR examination of the spine, referred to radiology with the clinical diagnosis of suspected tuberculous spondylitis, spondylodiscitis, or both. All of the non-contrast and contrast-enhanced MR results were read and interpreted by two independent observers, a musculoskeletal radiologist and a general radiologist, blindly. The interobserver agreement analysis of the MR examination was conducted using Kappa and McNemar test. RESULTS: : There was no significant difference between the contrast and non-contrast MR in diagnosing spondylitis (P= 0.368) and no significant difference in the interpretation of MR between the first and the second observer (P =  0.343). The concordance between the contrast and non-contrast spine MR in diagnosing spondylitis (R: 0.88, P < 0.001) and the interpretation of MR between both observers (R: 0.65, P < 0.001) were showed in this study. CONCLUSION: : There is a high concordance between the contrast and non-contrast MR in diagnosing tuberculous spondylitis. Although contrast MR is preferred as the standard imaging method of spondylitis, in case gadolinium contrast is unavailable, non-contrast MR can still provide valuable information in diagnosing spondylitis.